2020
DOI: 10.1002/mus.27069
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathies and vitamin D deficiency

Abstract: Randomized placebo-control trials of administrating either a topical compound containing vitamin D or oral open-label vitamin D 3 in patients with diabetic peripheral neuropathy demonstrated significant therapeutic benefits. 6 Vitamin D promotes axon regeneration and remyelination following nerve injury by modulating production of neurotrophins such as nerve growth factor. Nerve growth factor is necessary for sympathetic and sensory neuron survival and development. 9 Recognition of vitamin D deficiency is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…6 21 However, it has been reported that large and small fiber neuropathy develops in patients with Type 2 diabetes mellitus and hypovitaminosis D. 21 22 Vitamin D regulates axonal regeneration and remyelination by modulating neurotrophins. 5 6 22 Therefore, it is important to detect hypovitaminosis D in neuropathy cases. Although hypovitaminosis D is not the sole cause of neuropathy in healthy cases, it may be a facilitating factor in the presence of comorbid chronic diseases such as CF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 21 However, it has been reported that large and small fiber neuropathy develops in patients with Type 2 diabetes mellitus and hypovitaminosis D. 21 22 Vitamin D regulates axonal regeneration and remyelination by modulating neurotrophins. 5 6 22 Therefore, it is important to detect hypovitaminosis D in neuropathy cases. Although hypovitaminosis D is not the sole cause of neuropathy in healthy cases, it may be a facilitating factor in the presence of comorbid chronic diseases such as CF.…”
Section: Discussionmentioning
confidence: 99%
“…However, small-fiber changes cannot be displayed in the NCS. 6,21 However, it has been reported that large and small fiber neuropathy develops in patients with Type 2 diabetes mellitus and hypovitaminosis D. 21,22 Vitamin D regulates axonal regeneration and remyelination by modulating neurotrophins. 5,6,22 Therefore, it is important to detect hypovitaminosis D in neuropathy cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, these conditions can have a significant impact on the quality of life of patients. PNs causes can be different, like inherited and hereditary aspects, traumatic injuries, infections, metabolic problems, nutritional deficiencies, or toxic exposure, but also drugs or specific diseases can induce them (2)(3)(4)(5)(6)(7)(8). Sensorimotor polyneuropathies are often experienced by cancer patients (9), and these can be related to their oncologic condition, due to tumor invasion or compression exercised on nerves, or can be associated with a paraneoplastic effect (10).…”
Section: Introductionmentioning
confidence: 99%